1995. Implementation of Helicobacter pylori Stool Antigen Testing in a Large Metropolitan Centre: A Prospective Comparative Diagnostic Trial. (26th November 2018) - Fong, Evelyn; Nguyen, Hong; Kitt, Sharon; Guo, Maggie; Sabuda, Deana; Naugler, Christopher; Church, Deirdre; Pillai, Dylan
Abstract: Background: Clinical guidelines for H. pylori screening and post-treatment testing endorse the use of urea breath test (UBT), H. pylori stool antigen test (HpSAT), and biopsy-related tests. Due to protracted wait times at our patient service centers and non-compliance in children and elderly with complications for the UBT, we sought to compare UBT and HpSAT in the city of Calgary, Canada with a population close to 1.4 million people. Methods: To achieve this, a prospective diagnostic trial was performed comparing UBT to HpSAT in patients presenting with dyspepsia. A total of N = 150 patients agreed to undergo UBT ( 13 C-UBT kit, Helikit, Isodiagnostika Inc.) and consented to provide a stool specimen for simultaneous HpSAT testing (Diasorin LIAISON® XL H. pylori SA Monoclonal chemiluminescent immunoassay) in our centralized laboratory. Results: Our data show that concordant results were obtained in 148/150 (98.7%) patients with a positivity rate of 17.4%. One of two discrepants (UBT positive/HpSAT negative) resolved after repeat testing. Using UBT as the gold standard, HpSAT had a sensitivity of 96.30% (95% CI; 81.03% to 99.91%) and specificity of 100% (95% CI; 97.05% to 100.00%). A positive predictive value of 100% and negative predictive value of 99.2% (95% CI; 94.73% to 99.88%) was obtained. For patients where drug information was available, 38/130 (29.2%) had received an antibiotic associated with H. pylori in the preceding 12 months, with UBT and HpSAT providing concordant results in 37/38 (97.4%) of these individuals. Of note, 6/130 (4.6%) patients had received a specific combination anti- H.pylori treatment, and all 6/6 (100%) had concordant negative results suggesting successful eradication. A post-implementation economic evaluation of labor and materials associated with testing demonstrates a cost-savings of approximately USD5.47 per specimen in this locale. Conclusion: Our study confirms that HpSAT is a viable alternative to UBT for H. pylori screening in our jurisdiction with equivalent test performance and cost-savings. Pre- and post-implementation analysis of test compliance rates, waiting times, and test turn around times will also be presented. Disclosures: D. Pillai, Diasorin: None, Educational grant.